Rapıd Maxıllary Expansıon From Past To Present (Turkish Journal of Orthodontics, 2004)

(untitled)
The aim of our study is to evaluate effects of rapid maxillary expansion technique from past to present on respiratory system, general body health, together with dental and skeletal impression studies and also application varieties, effects on different age groups and alterations after expansion with historical order in its own course.